Epidemiological Study of Japanese Encephalitis Virus in Vientiane, Lao PDR, in 1990s - Mika Saito; Douangdao Soukaloun; Khampe Phongsavath; Bounlay Phommasack; Yoshihiro Makino (The Scientific World Journal)
Phylogenetic analysis of Japanese encephalitis virus (JEV) was conducted using core-premembrane and envelope gene sequence data of two strains from Vientiane, Lao People’s Democratic Republic, in 1993 and five from Okinawa, Japan, in 2002 and 2003, and previously published strains. The two Vientiane strains designated as LaVS56 and LaVS145 belonged to genotype 1 (G1) and the same subcluster of G1 as Australian strain in 2000, Thai strains in 1982–1985 and 2004-2005, and Vietnamese strain in 2005, but were distinct from the subcluster of recently distributing G1 strains widely in Asia including Okinawan strains and recent Lao strain in 2009. These clusters with own distinct distributions indicated involvements of different mechanisms and routes of spreading viruses and clarified that Australian G1 strain is from Southeast Asia, not from East Asia. Both Vientiane strains were antigenically close to P19-Br (G1, isolate, Thailand), but distinct from Nakayama (G3, prototype strain, Japan), Beijing-1 (G3, laboratory strain, China), and JaGAr#01 (G3, laboratory strain, Japan), demonstrated by cross-neutralization tests using polyclonal antisera. These results together with seroepidemiologic study conducted in Vientiane strongly suggest that diversified JEV cocirculated there in early 1990s.